Remarks on modal value - Wilkowski, Andrzej (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2013)
In this paper we talk about modal value, ideal modal and the relationship between stable distributions and the statistical characteristics like modal and ideal modal. The second part of this article is about the properties of normal and skew-normal density. In the third part of the article we present multiaverage. Multiaverage is an approximation of the random variable with more than just one point at the same time (which is important when we talk about random variables, which distributions are mixtures, or about multimodal densities). While defining multiaverage, we use standard moments method and some facts from orthogonal polynomial theory.
Mathematical Economics, 2013, Nr 9 (16), s. 105-116
Keywords: modal value; ideal modal; skew-normal density; multiaverage